1986
DOI: 10.1080/03079458608436274
|View full text |Cite
|
Sign up to set email alerts
|

Electrophoretic variation of avian rotavirus RNA in polyacrylamide gels

Abstract: SUMMARYFive different sorts of RNA profiles (electropherogroups 1 to 5) were recognised when avian rotavirus RNAs were electrophoresed in polyacrylamide gels. These could be distinguished from the RNAs of mammalian group A, B and C rotaviruses. Viruses belonging to electropherogroups 1, 2/3 and 4 were detected in chickens and viruses belonging to electropherogroups 1, 2, 3 and 5 were detected in turkeys. A minimum of three electropherogroups was recognised in each of four longitudinal surveys of broiler chicke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
3

Year Published

1988
1988
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 9 publications
2
11
0
3
Order By: Relevance
“…AvRV with the atypical RNA profile, characterized mainly by changes in the segregation characteristics of dsRNA segments 7, 8 and 9 were very frequent (21,26). Similarly, in this study AvRV with nine distinct electropherotypes was identified.…”
Section: Resultsmentioning
confidence: 71%
See 2 more Smart Citations
“…AvRV with the atypical RNA profile, characterized mainly by changes in the segregation characteristics of dsRNA segments 7, 8 and 9 were very frequent (21,26). Similarly, in this study AvRV with nine distinct electropherotypes was identified.…”
Section: Resultsmentioning
confidence: 71%
“…Even though there is no direct correlation between electropherotype and serotype, significant variations in eletrophoretic mobility of dsRNA segments can give rise to viral particles with antigenic variation in protein which induces neutralizing antibodies (21,26).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One was the obvious genomic difference between the pigeon and conventional group A mammalian rotaviruses. The electrophoretic migration profile of genomic RNA from our isolate most probably corresponds to the electrophero-group one described by Todd & McNulty (1986), although comparative co-electrophoresis experiments were not done. Another was the antigenic differences revealed by cross-neutralization tests between the pigeon virus and mammalian rotavirus.…”
Section: Discussionmentioning
confidence: 69%
“…This teschnique was also used to study avian rotaviruses from chickens (McNulty et al, 1981) and turkeys (Saif et al, 1985) and, according to the migration pattern on silver-stained PAGE, avian rotaviruses were classified into different eletropherogroups (Kang et al, 1986;Todd & McNulty, 1986) and eletropherotypes.…”
Section: Genome Electropherotyping By Polyacrylamide Gel Electrophoresismentioning
confidence: 99%